Taxonomic characterization and cytotoxic potential of Vietnamese Ganoderma ellipsoideum against human breast cancer MCF-7 cells - Trang Thi Thu Nguyen; Phu Tran Vinh Pham; Viet An Thi Nguyen; Trinh Thi Tuyet Nguyen; Linh Thuoc Tran; Phu Chi Hieu Truong; Manh Hung Tran (PLoS ONE, 2025)
This study reports for the first time the occurrence of Ganoderma ellipsoideum , a wood-decaying fungus, in Vietnam. Species identification was achieved through morphological characterization and sequencing of the internal transcribed spacer region of nuclear ribosomal DNA. Phylogenetic analysis confirmed that the Vietnamese specimens clustered within the Ganoderma ellipsoideum taxon, supported by high bootstrap and posterior probability values (90%/1.00). Morphological features further indicated its placement within the Ganoderma applanatum–australe complex. In vitro cytotoxicity assays revealed that the ethanol extract and its sub-fractions (n-hexane, ethyl acetate, aqueous) exerted inhibitory effects on human breast cancer MCF-7 cells, with the ethyl acetate fraction showing the strongest activity. In silico molecular docking demonstrated strong binding affinities between major triterpenoid compounds and key breast cancer-related proteins, including HPA, MELK, CK2α, and NUDT5. These findings not only establish Ganoderma ellipsoideum as a newly recorded species in Vietnam, but also suggest its promising potential as a source of anticancer agents.